The Influence of Social Media Content on Domestic Visit Intention at Candi Gedongsongo - Mutamakkinah, Haniatul; Badi’ah, Latifata Nuril; Ferdinand, Augusty Tae (Research Horizon, 2025)
This study aims to analyze the impact of social media content on the visit intention of domestic tourists to Gedongsongo Temple, with online reviews and social visibility acting as mediators. Based on Self-Congruence Theory, the research explores how the alignment between social media content and tourists' self-image can enhance personal engagement, ultimately driving visit intention. Using a quantitative approach with a survey, the study involves 113 respondents who have either visited or seen content about Gedongsongo Temple on social media, analyzed using Structural Equation Modeling (SEM-PLS). The findings indicate that appealing and authentic social media content increases online reviews that align with consumers' self-image, consequently boosting visit intention. Moreover, credible and informative online reviews about the destination also enhance social visibility and encourage more tourists to visit. Online reviews serve as a mediator that strengthens the relationship between social media content and visit intention. The social visibility gained through online reviews and interactions on social media amplifies the effect of social media content on tourists' intention to visit Gedongsongo Temple. These findings provide insights for destination managers to leverage authentic content and collaborations with influencers on social media to enhance destination appeal and attract tourists, supporting the sustainability of local tourism economies.